Enhancing Foreign Consumer Acceptance The Role of Capabilities of Creating Export-Market Oriented Products in Small and Medium-Sized Enterprises (SMEs) - Firmanzah Firmanzah (Gadjah Mada International Journal of Business, 2008)
The main purpose of this paper is to measure the effects of SMEs capabilities on their export performance. This paper offers a model to test the effects of the capabilities of creating export-market oriented products (EMOPs) on increasing SMEs’ export performance. Six hypotheses are developed to analyze causal effects of variables. Using 387 Indonesian SMEs as sample, hypotheses testing highlight the importance of SMEs’ capabilities of building export-market oriented products, which highly follow foreign (export) market standards. Hence, these kinds of products increase foreign consumer acceptance. In general, this paper offers a possible explanation to predict the determinants of how SMEs’ can perform in the export market.